Ba, Japanese-Style Knowledge Creation Concept: A Building Brick of Innovation Process inside Organization - Henry Pribadi (Institute of Research and Community Outreach - Petra Christian University, 2010)
Survival of a firm in industry will be primarily determined by how efficient it can harness competitive advantage from innovation process. Innovation process itself has strong correlation with knowledge creation, and to understand about innovation, people must understand about knowledge creation process. By successfully harnessing knowledge, people can use those resources to create some innovation product or service that in the end will provide competitive edge into the company. Unfortunately, not much research can be sought to provide more insight on the creation of knowledge inside a company. This paper explores about interesting concept of knowledge creation in Japanese term, which is called as “ba”. Ba concept can be used to describe how tacit knowledge and casual knowledge can be harnessed into a useful knowledge which in turn will be transformed into innovation process. This paper will briefly give some introduction about ba concept and how it is related to innovation process. A brief study of one multinational company will be used to describe how concept of ba is applied in understanding the success story of innovation from knowledge creation.